Niger : Food Security and Safety Nets - World Bank (Washington, DC, 2014)
Niger is a very poor country that faces serious problems of poverty and household food insecurity. With a per capita gross national income (GNI) of US$240 and an estimated 62 percent of the population living below the poverty line, Niger is one of the lowest-ranked countries on the United Nations' human development index. Reducing vulnerability and ensuring food and nutrition security is an overarching priority for the Government. Maintaining food security at the national and household level is an important priority for developing countries in general, both for the welfare of the poor and for political stability. In order to ensure food security, governments have adopted various strategies, including efforts to increase staple food crop production, market interventions, and a variety of safety net programs, especially during emergencies. In Niger, where profound vulnerabilities combined with a high level of population growth have resulted in endemic food insecurity, the Government is faced with a serious challenge. In this context, the purpose of this study is to contribute to the existing strategy and assist the Government in developing a holistic, multi-sectoral, and institutional approach to reducing the population's vulnerability to food insecurity. This report adds value to the ongoing policy discussions in two ways: first, it presents new empirical analysis of: i) food insecurity and vulnerability of households during the period of food crises as well as during normal period, ii) the structure and integration of cereal markets within Niger and with markets in neighboring countries, and iii) causes of the 2005 food crisis, and lessons learned on implications of various levels of cross-border flows between Niger and Nigeria. Second, it provides concrete short- and medium-term recommendations for helping government to improve the performance of existing programs to increase food security, particularly related to preparedness for and responses to food crises, and to design efficient safety nets mechanisms for vulnerable population.